Research and Practice on the Construction of the New Engineering Talent Cultivation System under the Metaverse Background - Ning, Yuhuan; Yan, Yumeng (International Journal of Social Sciences and Public Administration, 2025)
With the rapid growth of technologies like the metaverse, AI, and VR, traditional models for training new engineering talent face both challenges and opportunities. Current educational systems struggle with outdated curricula, a disconnect between industry needs and educational content, and limited teaching methods. This research explores how to optimize the talent cultivation system for new engineering disciplines within the metaverse context by integrating technology and education. The study highlights how metaverse technologies can enhance course diversity, practical learning, and student engagement, while also emphasizing the importance of interdisciplinary collaboration and industry synergy. Ultimately, the research proposes an innovative model for talent development, aiming to better align education with rapidly advancing technological needs.